Lateral canthotomy and cantholysis to relieve orbital compartment syndrome caused by a supraorbital hematoma - Andrew Yocum; Ross Ferrise; Erin L. Simon (JEM Reports)
Background: Lateral canthotomy is a procedure performed emergently for orbital compartment syndrome (OCS) when a patient's intraocular pressure (IOP) becomes elevated beyond 40 ​mmHg. This ophthalmologic emergency usually occurs from a mass effect within the orbit, commonly from retro-orbital pressure due to bleeding or hematoma. Often, this causes proptosis and stretching of the optic nerve. As the pressure increases, vascular perfusion decreases, causing pain and decreased vision. Supra-orbital injuries causing OCS are rare, making early clinical detection challenging. Proptosis may not occur at all. Definitive treatment of OCS involves lateral orbital canthotomy and cantholysis (LOC) to alleviate pressure and restore blood flow. Case report: A 65-year-old intoxicated male who presented to the emergency department after a ground-level fall. He was unable to report symptoms accurately and sustained a supraorbital hematoma while on clopidogrel. Despite lacking proptosis, the patient experienced a slow rise in IOP until peaking at 45 ​mmHg. Successful LOC resulted in immediate IOP reduction, and the patient was transferred for oculoplastic surgical evaluation. Why should an emergency physician be aware of this?: OCS is an ophthalmologic emergency; treatment within 2 ​h is recommended to avoid permanent vision damage. When a patient is unable to communicate visual symptoms after trauma near the orbits, serial IOP measurements must be taken, even in the absence of clinical signs, until OCS can be definitively ruled out. If pressure rises above 40 ​mmHg, then an emergent LOC is indicated. This unique case underscores the diagnostic challenges of supraorbital OCS and emphasizes the importance of prompt LOC in preventing irreversible vision damage.